Yermakova N. M. Referencial correlation of the eurysemantic word “thing” - Yermakova N. M. (Philological Treatises, 2020)
The summarized article defines the eurysemy as the lexico-semantic category, examines the functional peculiarities of the eurysemantic word thing in English and emphasizes its capacity to form set expressions. This article is aimed to show the ability of the word thing to reserve high degree of referencial correlation as a basic of phraseological units as well as to demonstrate the referential types of the basic word. Correspondingly two semantic components of the words were singled out i.e. denotational and referential as well as relevant definitions were given. The article also establishes the main mechanisms of forming semantics of the idioms with euryseme thing as the basic one. The article reveals that most of set expressions having the eurysemantic lexeme thing as the basic can denominate either generic or categorical meaning (as this single eurysemantic lexeme itself expresses). But the meaning of phraseological units is less abstract than the meaning of this lexeme because semantics of phraseological units always includes additional denotational-significative and/or connotative semes which narrow somewhat the semantics of the phraseological units in the context